Charades game: does it affect students’ learning on English vocabulary? - Aulia Rahmah; Yuli Astutik (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
The purpose of this study is to determine the effect of the use of charades game on elementary school students in improving English vocabulary as a foreign language. The source of the data in this study were 5th grade students of Madrasah Ibtidaiyah Nahdlatul Ulama Tropodo Sidoarjo, while the data  was the application of charades game to 5th grade students of Madrasah Ibtidaiyah Nahdlatul Ulama Tropodo before and after being given a test. Researchers use use pre-experimental quantitative design as the research method. This study uses one group pretest and posttest. The data obtained from the pretest and posttest which is analyzed by using the t-test formula. The results show that at the 5% level the t-test value is higher than t-table (tt) (4.53 2.024). Based on the test criteria, the results of the study show that there is a significant influence on the students' vocabulary skills after using charades game. It proves that charades game can improve the foreign language vocabulary of Islamic elementary school students, especially in Madrasah Ibtidaiyah Tropodo Sidoarjo. DOI: 10.26905/enjourme.v4i2.4258